RESERVATION SYSTEM DESIGN OF GOODS IN PT. BAYER - Lou Leni Sintawati; Ir. Sapta Aji SM, MM (Jurnal Sistem Informasi, 1998)
With the rapid advancement of information  technology world and the increasing demands for efficiency of presentation and effectiveness information for the smooth operations, it is not unreasonable if the PT. BAYER does not immediately apply the stuff with the computer reservation system. consideration among others when viewed from the company's assets are invested to operate a reservation system baranf very large, so that will greatly affect the survival of these goods ordering system if not properly managed and controlled.